Sistem Pendukung Keputusan Rekomendasi Pemilihan Calon Ketua BEM dengan Menggunakan Metode MOORA - Halomoan Hasibuan, Haposan; Laia, Sarpita; Mesran (ADA Research Center, 2025)
The Student Executive Board (BEM) is an official student organization that holds a strategic role as a forum for aspirations, advocacy, coordination, and the development of student potential in higher education institutions. The election of BEM chairman candidates at Universitas Budi Darma was previously conducted manually, making it less efficient and lacking systematic evaluation criteria. Therefore, this study aims to design a decision support system (DSS) for selecting BEM chairman candidates using the Multi-Objective Optimization on the basis of Ratio Analysis (MOORA) method. The MOORA method was chosen because it is capable of optimizing various conflicting criteria simultaneously. This study involved seven alternative candidates and seven criteria, namely leadership training (LDK), student activity, vision and mission, semester GPA (IPS), non-academic achievements, academic achievements, and semester level, with weights determined using the Rank Order Centroid (ROC) method. The collected data were then processed through normalization, weighting, and MOORA optimization calculations to determine candidate rankings. The results showed that out of the seven candidates, the best alternative was obtained by candidate A3 named Debby with a score of 0.4108. The implementation of this system proved to provide objective, fast, and accurate recommendations in determining the most suitable BEM chairman candidate. Thus, the MOORA method can serve as an effective solution to improve the quality of the BEM election process and support the enhancement of student organizational performance at Universitas Budi Darma.